Transforming Abandoned Sand Pits into Sustainable Aquaculture Ponds in Purba Medinipur, West Bengal, India - Sinha, Nibedita; Payra, Pijush; Saxena, Shriparna (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study was based on aquaculture possibilities in abandoned sand pits through scientific pond preparation and management. The research work was conducted at Depal, Purba Medinipur, West Bengal. In the district of Purba Medinipur sand mining activity were primarily carried out for the purpose of house construction and for land filling. In this district about 100 ha abandoned sand mining pits are present. Generally, ponds are manmade impoundments mainly used for water harvesting and for aquaculture. Pond preparation is the basic and utmost important step in freshwater aquaculture to enhance the fish production. After sand mining activity abandoned low laying pits are filled by rain water and creates pond environment. Following APHA (American Public Health Association) guideline, the physico-chemical parameters of soil and water were analysed every 30 days interval to ascertain how the parameters change with change with the season. Here scientific managements and higher percentage of organic manures like cow dung and mohua oil cakes were applied to increase the water holding capacity and fish production of the pond. This treatment helps to increase the average values of NPK from 16.52 mg/100gm, 1.93 mg/100gm and 1.50 mg/100gm to 28.69 mg/100gm, 5.61 mg/100gm and 11.92 mg/100gm respectively. Organic Carbon (%) and Specific Conductivity (µS/cm) was also increased. Lime was also applied in higher amount to correct the pH of both soil and water and to kill parasites. Soil pH and Free Calcium Carbonate (%) was corrected and become ideal for aquaculture.